Repolarization of Tumor-Infiltrating Myeloid Cells for Augmentation of CAR T Cell Therapies - Luo, Weichuan; Napoleon, John V.; Zhang, Fenghua; Lee, Yong Gu; Wang, Bingbing; Putt, Karson S.; Low, Philip S. (Frontiers in Immunology, 2022)
Although CAR T cell therapies have proven to be effective in treating hematopoietic cancers, their abilities to regress solid tumors have been less encouraging. Mechanisms to explain these disparities have focused primarily on differences in cancer cell heterogeneity, barriers to CAR T cell penetration of solid tumors, and immunosuppressive microenvironments. To evaluate the contributions of immunosuppressive tumor-associated macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs) on CAR T cell efficacies, we have exploited the ability of a folate-targeted Toll-like receptor 7 agonist (FA-TLR7-1A) to specifically reactivate TAMs and MDSCs from an immunosuppressive to pro-inflammatory phenotype without altering the properties of other immune cells. We report here that FA-TLR7-1A significantly augments standard CAR T cell therapies of 4T1 solid tumors in immune competent mice. We further show that co-administration of the FA-TLR7-1A with the CAR T cell therapy not only repolarizes TAMs and MDSCs from an M2-like anti-inflammatory to M1-like pro-inflammatory phenotype, but also enhances both CAR T cell and endogenous T cell accumulation in solid tumors while concurrently increasing their states of activation. Because analogous myeloid cells in healthy tissues ar not altered by administration of FA-TLR7-1A, no systemic activation of the immune system nor accompanying weight loss is observed. These data argue that immunosuppressive myeloid cells contribute prominently to the failure of CAR T cells to eradicate solid tumors and suggest that methods to reprogram tumor associated myeloid cells to a more inflammatory phenotype could significantly augment the potencies of CAR T cell therapies.